The Pivotal Role of Invasive Functional Assessment in Patients With Myocardial Infarction With Non-Obstructive Coronary Arteries (MINOCA) - Mangiacapra, Fabio; Viscusi, Michele Mattia; Paolucci, Luca; Nusca, Annunziata; Melfi, Rosetta; Ussia, Gian Paolo; Grigioni, Francesco (Frontiers in Cardiovascular Medicine, 2021)
Myocardial infarction with non-obstructive coronary arteries (MINOCA) encompasses several pathophysiological mechanisms not yet fully understood. Among the latter, vasomotion abnormalities and coronary microvascular dysfunction (CMD) play a major role for both epidemiological and prognostic reasons. Despite current guidelines do not recommend routine physiological assessment of both epicardial and microvascular coronary compartments within the context of an acute myocardial infarction, several recent evidence support the critical role of a comprehensive invasive functional assessment in order to identify the underlying pathophysiological mechanism and consequently to select an appropriate therapeutic strategy. Unfortunately, optimal medical therapy for these patients is not currently established due to the lack of dedicated trials evaluating clinical outcomes of commonly used medications for secondary prevention in MINOCA patients. For this reason, additional research is warranted to provide personalized treatments for patients affected by this puzzling clinical entity.